Odgovornost notarja - Podgoršek, Bojan (Pravni letopis, 2008)
Although the notary service is a public service, the legal relation between the notary and his client has some characteristics of an order agreement (mandatory agreement). The notary's obligations are stipulated by law and are a component part of the notary's legal relationship with his clients, who are persons placing the notary order. Breaching of theese obligations is one of the cases of notary's indemnification responsibility. The notary's unbusinesslike (delinquent) indemnification responsibility can also occur in the relation with possible third persons, who are not persons placing the notary order. Regardless of the definition of the notary's responsibility (businesslike or unbusinesslike) it is stipulated in both cases that the notary is relieved of his responsibility if he proves that in fulfilling his legal obligations he acted with appropriate professional care (with good notary care).
Keywords: notarji; odgovornost; odškodninska odgovornost